1986
DOI: 10.1007/bf01975884
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin in human milk

Abstract: Human milk trypsin was purified by adsorption chromatography on cellulose-bound 4-aminobenzamidine; its molecular weight was about 24,000 daltons. Its concentration determined by a radioimmunoassay varies between 2.9 and 5.6 micrograms/l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…However, to our knowledge, trypsin and thrombin activity in human milk have never been demonstrated. One study (42) found that isolated trypsin from human milk is active against a trypsin substrate (benzoyl-L-arginine p-nitroanilide). The activity of isolated trypsin, however, does not imply activity within milk because milk contains a s1antitrypsin.…”
Section: Figurementioning
confidence: 98%
“…However, to our knowledge, trypsin and thrombin activity in human milk have never been demonstrated. One study (42) found that isolated trypsin from human milk is active against a trypsin substrate (benzoyl-L-arginine p-nitroanilide). The activity of isolated trypsin, however, does not imply activity within milk because milk contains a s1antitrypsin.…”
Section: Figurementioning
confidence: 98%
“…This milk trypsin, sometimes referred to as anionic trypsin, was detected in human milk by immunodiffusion and immunoelectrophoresis (72). When comparing the amino acid sequences of anionic trypsin with that of trypsin 1 and 2 (using BLAST in Uniprot), we found that anionic trypsin has the same sequence as trypsin 2 (anionic trypsin is likely an older name).…”
Section: Proteolytic Systems In Milkmentioning
confidence: 99%
“…When anionic trypsin (trypsin-2) is isolated from human milk, it is active (demonstrated by splitting the chromogenic substrate benzoyl-DL-arginine- p -nitroanilide) (72). However, in the context of milk, trypsin seems to have no activity (72).…”
Section: Proteolytic Systems In Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides having termini that pass a comparison to an enzymatic specificity have their abundances added to the sum of the respective enzyme. Proteases known to be present in milk include plasmin (48), trypsin (49,50), elastase (50), cathepsin-D (51), and thrombin (39). In addition, undefined carboxy/amino peptidases have been proposed to act in milk (20).…”
Section: Nano-lc Mass Spectrometry Analysis Of Endogenous Peptides Inmentioning
confidence: 99%